Estimasi Daya Gabung Galur Jagung Manis (Zea mays saccharata Sturt) Pada Karakter Kegenjahan Dan Hasil Dengan Menggunakan Genotipe+Genotipe x Environment (GGE) Biplot - Syihab, Fakhri Nasharul; Karuniawan, Agung; Ismail, Ade; Yuwariah, Yuyun; Ruswandi, Dedi (Jurusan Agroteknologi, 2024)
Sweet corn is an important commodity in Indonesia, but its productivity is low due to the use of seeds that have undergone genetic degradation. This research aims to estimate general combining ability (GCA) and spesific combining Ability (SCA) on maturity characteristics and sweet corn yield. The research was conducted in Cikajang Village, Garut Regency, from April to July 2023, using a randomized block design with 40 treatments repeated three times. Analysis was carried out using the Genotype + Genotype x Environment (GGE) Biplot method. The variance results showed a significant effect of line, tester, and line x tester interactions on male flowering age, female flowering age, harvest age, and yield. From the GGE Biplot analysis, the